Association of phenylthiocarbamide taste blindness trait with early onset of childhood obesity in Mysore - YS, Saraswathi; Najafi, Mohsen; VS, Vineeth; P, Kavitha; Malini, Suttur S (Archives of Advances in Biosciences, 2011)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> Ability to taste Phenylthiocarbamide (PTC) a bitter compound is widely used to know the heritable trait in both genetic and anthropological studies. The study is based on the ability of a person to sense the taste of PTC. Inability to taste has also been associated with medical illness not typically with taste impairment, so far no study has yet proved whether PTC blindness correlates with childhood obesity. This study is the first attempt to examine PTC sensitivity in obese children and healthy children to determine variation in the perception of bitter tastes which is associated with eating behavior, body mass index, and childhood obesity. The present investigation is carried out in Mysore, during years 2008 - 2009. Phenylthiocarbamide taste sensitivity was measured by administering PTC solution for obese and control children by modified method of Harris and Kalmus. The result focused that tasters were significantly more frequent (67%) than non-tasters (33%) in control population. A higher proportion of non-tasters were observed in obese children (72%) when compare to non-obese subjects (28%). These differences were not explained by alterations in perception of basic taste sensitivity or age. Increased frequency of non-taster allele is evident in children with obese condition. This could be due to lack of preference for food among non-tasters. As the phenotypic variation in PTC sensitivity is genetic in origin, it may represent a surrogate risk factor for the development of childhood obesity.